KINERJA PORTOFOLIO SAHAM BERDASARKAN SAHAM PERUSAHAAN ORANG KAYA INDONESIA MENURUT FORBES DI BURSA EFEK INDONESIA - Sari, Fenita Dwi; Purbawangsa, Ida Bagus Anom; Artini, Luh Gede Sri (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.04.TAHUN 2017, 2017)
The increasing of the public interest to invest in the stock market transactions, by arranging the stock portfolio. Stock portfolio will be prepared using stocks - shares of companies that go public in Indonesia Stock Exchange belong to the richest people in Indonesia according to Forbes Indonesia edition April 2013. As a matter of evaluation, this study was conducted in order to determine the result of establishment of a stock portfolio return which is based on public information compared to the market return. The variables in question is a stock portfolio return and the market return. This study compared the return of stock portfolio which is based on public information in April 2013 with the return of stock portfolio for each period of 3 months within 1 year ahead . The population used is the price of securities and the company stock market owned by 25 richest people in Indonesia by Indonesia edition of Forbes magazine April 2013. The sample is using census method by using the entire population. Stock data obtained from the Indonesia Stock Exchange.
Keywords: portfolio , return, performance, risk.